Ventilacija podhlajenih - Mekjavić, Igor B. (Medicinski razgledi, 2002)
This study evaluated the benefits of a heat and moisture exchanger in the oro-nasal mask of a ventilating balloon for resuscitation in sub-zero ambients. Specifically, it tested the hypothesis that the reduction of respiratory heat loss would be similar to that achieved with mouth-to-mouth resuscitation. The prototype respiratory heat and moisture exchanger developedto minimise respiratory heat loss in subzero ambients was evaluated at ambient temperatures (Ta) of -20degreesC, -10degreesC, 0degreesC,10degreesCand 20degreesC. It comprised a thermally insulated oro-nasal mask with a cylindrical heat and moisture exchanging unit protrudingfrom the centre of the mask. The heat exchanging unit contains a honeycombĆ aluminium structure, providing a total surface area of 478.5 cm2 for the exchange of heat and moisture between the inhaled and exhaled air. A simulator comprising a hydraulically driven pump and a humidifier provided a ventilatory rate of 11.25 Lžmin. The simulated exhaled volume of air was maintained at approximately 37 degrees C and saturated with water vapour. The HME was strapped to the head of a manikin, whose mouth was connected to the respiratory simulator. The entire arrangement was placed in a climatic chambermaintained at the desired temperature. At ambient temperatures ranging from -24degreesC to +22degreesC, the HME elevated the temperature of the inhaled air to within the range of +22degreesC to +29degreesC. The humidity ofthe inhaled air was maintained at 100% in all conditions. The results indicate that the HME effectively reduces respiratory heat loss in ambient conditions ranging from -20 to +20degreesC. An oro-nasal mask incorporating a heat and moisture exchanger would therefore be capable of significantly reducing respiratory heat loss during ventilation of hypothermic victims.
Keywords: hipotermija; podhlajenost; ogrevanje; ventilacija; dihalni balon